Effectiveness of Economic Value Added, Earnings Per Share, Market Share and Institutional Ownership on Stock Returns in Companies Listed on the IDX80 Index of the Indonesia Stock Exchange - Vani Alicia Napitupulu; T. Alvi Syahri Mahzura; Sari Nuzullina Rahmadhani (Jurnal Ilmiah Akuntansi Keuangan dan Bisnis (JIKABI), 2022)
This study aims to determine the Effect of Economic Value Added (EVA), Earnings Per Share (EPS), Market Share and Institutional Ownership on Stock Returns in Companies Listed on the IDX80 Index of the Indonesia Stock Exchange for the 2019-2021 Period. The population used in this study was 80 IDX80 companies listed on the Indonesia Stock Exchange. The sampling method is to use the census method. The sample used was 240 companies. The analysis techniques used are normality test, multicollinearity test, autocorrelation test, heteroskedasticity test, multiple linear regression analysis, multiple correlation coefficient test, F test, t test and determination coefficient test.Based on the test results of classical assumptions, it is known that the data are normally distributed and there are no symptoms of multicollinearity, autocorrelation and heteroskedasticity. The results of the coefficient of determination test showed an R2 value of 0.699 which means that 69.9% of the influence of bound variables can be explained by other variables that were not used in this study. Based on the results of the F test, it is known that together free variables affect bound variables. And based on the results of the t test, it is known that the free variables, namely Economic Value Added, Earnings Per Share and Institutional Ownership have a partial effect on the Stock Return variable while the Market Share variable does not partially affect the Stock Return variable.